2023
DOI: 10.1101/2023.01.06.522977
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Omicron Spike Protein Is Vulnerable to Reduction

Abstract: SARS-CoV-2 virus spike (S) protein is an envelope protein responsible for binding to the ACE2 receptor, driving subsequent entry into host cells. The existence of multiple disulfide bonds in the S protein makes it potentially susceptible to reductive cleavage. Using a tri-part split luciferase-based binding assay, we evaluated the impacts of chemical reduction on S proteins from different virus variants and found that those from the Omicron family are highly vulnerable to reduction. Through manipulation of dif… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(96 reference statements)
0
4
0
Order By: Relevance
“…Although these disulfide bonds are conserved in all variants of concerns, Yao et al have revealed that some disulfides in the RBD of Omicron S protein, such as C480-C488 and C379-C432, are susceptible to reduction that could affect binding capacity and stability of the protein( 49 ). To understand whether mutations of Omicron S affect the formation of disulfide bonds, we examined and compared the disulfide bonds of the S proteins of Omicron with the D614G variant using mass spectrometry analysis with four various enzyme digestion methods.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although these disulfide bonds are conserved in all variants of concerns, Yao et al have revealed that some disulfides in the RBD of Omicron S protein, such as C480-C488 and C379-C432, are susceptible to reduction that could affect binding capacity and stability of the protein( 49 ). To understand whether mutations of Omicron S affect the formation of disulfide bonds, we examined and compared the disulfide bonds of the S proteins of Omicron with the D614G variant using mass spectrometry analysis with four various enzyme digestion methods.…”
Section: Resultsmentioning
confidence: 99%
“…The disulfide bond between C840 and C851 in the fusion peptide of S protein also can facilitate the binding between this peptide and cell membrane (48). A recent study has revealed that mutations in the RBD domain of the Omicron S protein affect the stability of two disulfide bonds, elevating the vulnerability of this S variant to reduction (49). Our aim in the present study was to better understand the structural characteristics and changes of the SARS-CoV-2 Omicron S protein (S-Omicron) relative to the S protein of the D614G variant (S-D614G).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The E484A mutation of Omicron variant in Benin has ∆∆𝐸 < 0, which means an increased binding affinity of hACE2. Especially, Yao et al (2023) showed that changes to the positively charged side chains of E484A and T478K enormously changed the redox of the disulfide bond, leading to a decrease in the stability of the RBD structure. Therefore, Spike-hACE2 complex structure of Omicron in Benin has the highest RMSD (Table 3).…”
Section: Discussionmentioning
confidence: 99%